2012
DOI: 10.1021/jp211435b
|View full text |Cite
|
Sign up to set email alerts
|

Pnicogen–Hydride Interaction between FH2X (X = P and As) and HM (M = ZnH, BeH, MgH, Li, and Na)

Abstract: A pnicogen-hydride interaction has been predicted and characterized in FH(2)P-HM and FH(2)As-HM (M = ZnH, BeH, MgH, Li, and Na) complexes at the MP2/aug-cc-pVTZ level. For the complexes analyzed here, P(As) and HM are treated as a Lewis acid and a Lewis base, respectively. This interaction is moderate or strong since, for the strongest interaction of the FH(2)As-HNa complex, the interaction energy amounts to -24.79 kcal/mol, and the binding distance is equal to about 1.7 Å, much less than the sum of the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
82
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 67 publications
1
82
0
1
Order By: Relevance
“…CH 3 , in the Be and Mg hydrides tends to increase the absolute value of the V S,min , while a reverse trend is obtained for the electron-withdrawing F substituent. Thus, the hydrogen atom in the metal hydrides can act as a potential negative site for an electrophilic attack, which has been previously evidenced in numerous theoretical studies [57][58][59].…”
Section: Isolated Monomersmentioning
confidence: 82%
“…CH 3 , in the Be and Mg hydrides tends to increase the absolute value of the V S,min , while a reverse trend is obtained for the electron-withdrawing F substituent. Thus, the hydrogen atom in the metal hydrides can act as a potential negative site for an electrophilic attack, which has been previously evidenced in numerous theoretical studies [57][58][59].…”
Section: Isolated Monomersmentioning
confidence: 82%
“…They also investigated the complexes formed between the acids O = PH 3 , S=PH 3 , HN=PH 3 , H 2 C = PH 3 and phosphorus, nitrogen bases [29]. Some pnicogen bonding interactions related to σ-hole and π-hole [30][31][32], single electron [33], and hydride [34] were predicted and characterized. It has been demonstrated that the pnicogen bond is relevant in biological systems and can control self-assembly processes that yield the formation of macrocycles [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…They were studied all the time because of their extensive potential utilization in diverse fields such as molecular recognition, drug design, crystal engineering, and versatile materials [2][3][4][5][6][7][8][9]. Among these interactions, the hydrogen bond and halogen bond are probably most frequently and thoroughly investigated [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%